Contribuições para a incorporação da linguagem tecnológica da informação e comunicação no contexto educacional - Nascimento, Genoveva Batista do (2006)
This research brings considerations about the technological language incorporated in the educational context, but specifically we approach the challenges that the Digital Technologies - TDIC present, in conceptual terms in the education field. Is a study case with specialization egresses pupils in education and communication and information s technologies - CETIC of UFPB in the year 2004/2005. Have the objective of contribute for the reflection on the used technological language in the education process mediated for the technology. The data had been gotten through the sending for electronic mails, of a research instrument to the pupils who already meet in the teaching activity. Through a qualitative boarding it was looked to describe and to explain the studied reality. We detach the importance of the understanding and appropriation of the technological language for the professors and, as resulted, we point that the incorporation of the technological language in the pedagogical process if configures as a new ability for the professor.